Mathematical analysis of the incompressible Euler and Navier-Stokes equations : an introduction - Bedrossian, Jacob; Vicol, Vlad (Providence : American Mathematical Society, 2022)
The aim of this book is to provide beginning graduate students who completed the first two semesters of graduate-level analysis and PDE courses with a first exposure to the mathematical analysis of the incompressible Euler and Navier-Stokes equations. The book gives a concise introduction to the fundamental results in the well-posedness theory of these PDEs, leaving aside some of the technical challenges presented by bounded domains or by intricate functional spaces.
Includes bibliographical references (pages 199-216) and index.
Keywords: Fluid dynamics; Navier-Stokes equations; Partial differential equations; Equations of mathematical physics and other areas of application -- Euler equations; Equations of mathematical physics and other areas of application -- PDEs in connection with fluid mechanics; Fluid mechanics -- Incompressible inviscid fluids; Hydrodynamic stability -- Parallel shear flows